Eskatologis Sebagai Tema Sentral Alquran: (Kajian Munasabah Surah Qaf Sampai Al-Waqiah) - Tilawati, Anis (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2023)
This research examines eschatology as a central theme in the Quran through a munasabah (correlation) approach focusing on three consecutive surahs: Qaf, Al-Dzariyat, and Al-Waqiah. This study identifies and analyzes the eschatological thematic coherence between these three surahs using content analysis and thematic interpretation methods. Results show that these surahs possess a unified eschatological theme that develops progressively: Surah Qaf establishes the possibility of resurrection, Al-Dzariyat emphasizes its certainty, and Al-Waqiah describes the event and its impacts in detail. This interconnection strengthens the argument that eschatology constitutes a central theme of the Quran conveyed through carefully organized literary structures. These findings contribute to a deeper understanding of the Quran's internal coherence and the significance of eschatology in its core message.